The Families of Students with Multiple Disabilities in the Educational Process - Kantor, Jiří; Ludíková, Libuše (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper focuses on several aspects of the relationship between families of students with multiple disabilities and the educational process. Quality-based methodology was used for the research due to a lack of sufficient theoretical background in this area. The objective of the paper was to elucidate the significance of education of students with multiple disabilities for their families and to describe the process of cooperation between these families and the teachers. This paper uses data and outputs from a qualitative analysis of education of students with severe multiple disabilities (semi-structured interviews with 45 teachers of students with multiple disabilities, observation of 4 students in the educational process and an analysis of 30 samples of educational documents using open, axial and selective coding). The resulting theory was combined with the results of a survey focused on the cooperation between the families and the teachers in order to gain a saturated data sample. This survey used semi-structured interviews with 5 teachers of students with multiple disabilities. The data from these interviews were analysed by means of open coding, compared with the outputs of the previous research and a theoretical model for educational intervention with the families of students with multiple disabilities was constructed and described. This model offers ideas for educational practice as well as further research.